The equation of a parabola can be represented as:
(x - h)^2 = 4p(y - k)
Where (h, k) is the vertex and p is the distance from the vertex to the focus.
Given the vertex (-3, -4) and the focus (-3, -3), we can see that p = 1.
Therefore, we can substitute the values into the equation:
(x + 3)^2 = 4(1)(y + 4)
Simplifying gives us:
(x + 3)^2 = 4(y + 4)
This is the equation of the parabola with the given vertex and focus.
Write an equation of a parabola with the given vertex and focus.
Vertex: (-3, -4)
Focus: (-3, -3)
1 answer